المسؤولیة البیئیة في المؤسسات الاقتصادیة الجزائریة بین الالتزام الأخلاقي والمساءلة القانونیة - فلاق، محمد Fellaq, Mohammed; حدو، سميرة أحلام; خرشي، إسحاق (جامعة العربي بن مهيدي أم البواقي - مخبر المالية، المحاسبة، الجباية والتأمين, 2018)
The environment in Algeria between ethical responsibility and legal accountability. Although there is a set of rules, mechanisms and preventive interventions for the protection of the environment in Algeria, However, environmental degradation continues, as indicated by national reports on the state of the environment Which raises a main question regards the effectiveness and Efficiency of preventive mechanisms for the protection of the environment to prevent this deterioration? Or is there ecological disaster prevention and cannot be predicted by natural factors due to shortcomings in the implementation of preventive mechanisms? Which leads us to wonder again about whether we need to apply the rules and correctional interventions for the environment, through the development of ethical responsibility and the application of the rules of the legal and criminal accountability? Through a descriptive analytical approach, this paper reviews the situation of The environment in Algeria between ethical responsibility and legal accountability. The paper concludes with some recommendations for continuous improvement in the environmental field at various levels.
بالرغم من وجود ترسانة من القواعد والآليات الوقائية والآليات الوقائية والتداخلية المتعلقة بحماية البيئة في الجزائر، إلا أن التدهور البيئي لا يزال مستمر كما تشير إليه التقارير الوطنية حول حالة البيئة، الأمر الذي يثير تساؤلا جوهريا يتعلق بمدى فعالية وكفاية الآليات الوقائية لحماية البيئة لاتقاء هذا التدهور؟ أم أن هناك كوارث لإيكولوجية لا يمكن اتقائها وتوقعها بفعل العوامل الطبيعية بسبب قصور في تنفيذ الآليات الوقائية؟ الأمر الذي يجرنا إلى التساؤل من جديد عن ما إذا كنا بحاجة إلى تطبيق القواعد التدخلية والإصلاحية للبيئة، من خلال تنمية المسؤولية الأخلاقية وتطبيق قواعد المساءلة القانونية والجنائية؟ من خلال منهج وصفي تحليلي تستعرض هذه الورقة حالة البيئة في الجزائر. وتخلص الورقة إلى تقديم بعض التوصيات للتحسين المستمر في المجال البيئي على مختلف مستوياته.
Keywords: المسؤولیة البیئیة; المسؤولية الأخلاقية; المساءلة القانونیة